Detection and quantification of vitamins in microliter volumes of biological samples by LC‐MS for clinical screening. Issue 10 (10th July 2018) - Khaksari, Maryam; Mazzoleni, Lynn R.; Ruan, Chunhai; Song, Peng; Hershey, Neil D.; Kennedy, Robert T.; Burns, Mark A.; Minerick, Adrienne R.
Abstract : A method for simultaneous determination of water‐soluble vitamins B1, B2, B3 (nicotinamide), B5, B6 (pyridoxamine), B9 and fat‐soluble vitamins E (α‐tocopherol) and K1 in tears, and B1, B2, B3, B5, B6, B9, A (retinol), and E in blood serum is described. Liquid chromatography‐mass spectrometry (LC‐MS) was used with a ternary mobile phase of water and acetonitrile containing 0.1% formic acid and methanol containing 5 mM ammonium formate. Vitamins were quantified using an internal standard method. Using 25 μL injection volumes, the limits of detection were in the range of 0.066‐5.3 ng in tear, and 0.087‐1.1 ng in serum with linear responses for all vitamins. Intra‐ and inter‐day precision and recoveries were satisfactory. This is the first study to demonstrate simultaneous vitamin detections in microliters of biological samples which has distinct advantages in many diagnostic applications with limited available fluids (e.g., tears; elderly anemic blood) or sampling small subjects (e.g., rodents). © 2018 American Institute of Chemical Engineers AIChE J, 64: 3709–3718, 2018